A Randomized Controlled Trial of a Mobile Application to Improve HIV Preventive Behaviors among Youth Men Who Have Sex with Men in Thailand - Unrit, Kengkaj; Glangkarn, Sumattana; Promarak, Terdsak (National Journal of Community Medicine, 2026)
Background: Human Immunodeficiency Virus (HIV) remains highly prevalent among young men who have sex with men (YMSM), necessitating innovative, theory-driven prevention strategies. The objectives of this study were to evaluate the effectiveness of a Cognitive Behavioral Group Counseling (CBGC)-based mobile application in improving HIV prevention knowledge, attitudes, and behaviors among YMSM. Methods: A randomized controlled trial was conducted among 60 YMSM aged 18-24 years, allocated equally into experimental and control groups. The intervention group received a CBGC-based mobile application over 10 weeks, followed by 14 weeks of follow-up. Outcomes were assessed using validated questionnaires measuring knowledge, attitudes, and preventive behaviors. Data were analyzed using paired and independent t-tests with a significance level of 0.05. Results: The experimental group demonstrated significant improvements in HIV prevention knowledge, attitudes, and behaviors compared to the control group. Post-intervention scores were significantly higher in the intervention group, with notable increases in high-level knowledge, positive attitudes, and consistent preventive practices. No significant changes were observed in the control group. Conclusion: The CBGC-based mobile intervention was effective in enhancing HIV preventive outcomes among YMSM. Digital, theory-based interventions offer a promising approach for targeted HIV prevention in high-risk youth populations.